Αγγλικά - Ανακαλύπτουμε τα ταλέντα μας (What are you good at?) - Δ'-Ε΄Δημοτικου Επ. 34 (Υπουργείο Παιδείας και Θρησκευμάτων, 2021)
: [♪ Μουσική Έπηρε Ψωμακή Μουσική Μουσική υπέροχης Απροκλήματος Μουσική Μουσική Εκφώνησης Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική ΤΟ ΜΤΘΟΝΤΚΟΣΗΣΤΗΣΤΗΣΩΣΗΣΟΣΗΣΗΣΕΣΗΣΗΣΗΣΗΣΟΣΗΣΗΣΗΣΣΗΣΗΣΤΗΣ What are you feeling today? You feeling good? You feeling great? Or are you feeling fantastic? I'm feeling fantastic and today we are going to learn something amazing. We are going to learn what are we good at. Now, let's start with a game. I've got a word in my mind. Can you guess my word? I've said this word before. Think a little bit. My word starts from the letter G. And which one do you think is the last letter? Exactly, it is the letter D. So my word starts from G and ends in D. I'll help you a little bit more. Is it better now? Can you find my word? Exactly. My word is the word good. Good. We can say, today I'm good. Or we can say, what are we good at? My students are good at many, many things. And I'm sure you are good at many things as well. Do you want to meet my students? Let's go. This is Diana. She's great at cooking. She doesn't like sport very much. She doesn't sing but loves music. Are you like Diana? Are you good at cooking? Do you like music? Let's see my next student. This is Lee. He's great football player. He loves pizza but doesn't cook. He plays the piano a little. So we can say that Lee is good at football. He likes to cook but he's not good at cooking. And he plays the piano a little. And this is Mike. He can sing really well. He likes to help his mum to cook and does judo. So Mike is good at singing and he's good at judo. Do you like judo? So let's have a look again. I told you before that my students are good at many things. Diana is great at cooking. Mike likes to help his mum to cook. Lee loves pizza but doesn't cook. So which of the three students is good at cooking? Exactly. Diana is good at cooking. Now let's see if you remember. Who's good at football? Is Diana good at football? Or maybe Mike? Hmm. Do you think Lee is good at football? Let's have a look. Diana doesn't like sport. So can Diana be good at football? Don't think so. Mike does judo. And Lee is a great football player. So you were right. Lee is good at football. Now let's see if you remember who's good at singing. Do you remember? Diana is good at cooking. And she likes music. But is she good at singing? I don't remember. Do you? Mike. Do you think Mike is good at singing? And what about Lee? We said that Lee is good at football. Can he be good at singing too? Of course he can. But let's see who of my students is good at singing. Do you remember Diana? Of course you do. And we said that Diana is good at... Exactly. She's good at cooking. She doesn't like sport very much. And she doesn't sing. But loves music. So Diana is not good at singing. And this is Lee. He's a great football player. He loves pizza but doesn't cook. He plays the piano a little. So is Lee good at singing? No, he's not. And this is Mike. He can sing really well. And he likes to help his mum to cook. And he also does judo. So yes, you were right. Mike is good at singing. Are you good at singing? Well, I'm not very good at singing. But I love to sing. Now the thing is that we are all champions. We are all very good at something. We are champions outside in the playground. We are champions at school. And we are champions at home. And you can be good at many, many things. And I'm sure you are. But now you might ask me, how can we be champions outside? And how can we be champions at home? And how can we be champions at school? Let's find out together. We can try to be a good friend. We can try to be a good child. We can try to be a good grandchild. We can try to be a good student. And we can try to be a good brother or sister. Are you a good friend? Are you a good child? Are you a good grandchild? Are you a good student? Are you a good brother or sister? I'm sure you are. Let's have a look at this picture. What can you see? Can you see a good friend? Can you see a good child? Can you see a good grandchild? Can you see a good student? Or maybe a good brother or sister? That is absolutely right. You can see a good brother or sister. But what does it mean to be a good brother or sister? How can we be good brothers or sisters? You can try to be a good brother or sister by playing together and helping your brothers or sisters. So remember, if you have a brother or a sister, play together and help them. Now, what do we see in that picture? Can you see a good friend? Can you see a good child? Or maybe a good grandchild? Is that a good student? Or a good brother or sister? Look at the picture very carefully. What can you see? I can see a grandma and a child. So, I see a good grandchild. Very well done. And how can we be good grandchildren? That might be tricky sometimes. Let's see together. You can be a good grandchild by calling your grandma and grandpa and say, I love you grandma, I love you grandpa. Remember to call your grandparents every week and tell them how much you love them. That is really important. Now, let's look at that picture. What can we see there? I can see a mummy and I can see a daddy. And I can also see a child. So what do you think? Is that a good friend? A good child? A good grandchild? A good student? Or a good brother or sister? You're right. This is a good child. How can we be good children? Sometimes we forget how we can be good children. So let's see together. If we want to be good child, we can help our mum and dad every day at home. We can help them tidy the house or we can help them cook. We can help them walk the dog. Or we can help them wash their cars. So remember, if you want to be a good child, you need to help your mum and dad at home. Now, what can we see in that picture? I see many kids together. And they are around a laptop. Maybe they're studying something. So what do you think we've got there? Have we got a good friend? A good child? A good grandchild? A good student? Or a good brother or sister? Look at the picture carefully. The children are wearing school uniforms. Can you see that? Exactly. They are students. So in that picture, we can see some students wearing the school uniforms. But how can we be good students? Let's see. If we want to be good students, we need to try hard at school. Because trying hard and doing our best is what makes us champions at school. Are you trying your best? Are you trying very hard? I'm sure you are. Now this picture. This is one of my favourite pictures. What can we see there? I think that we can see a good grandchild. That's right. Of course it's not. We can see grandparents in that picture. Maybe. Are these good friends? Yes, they are. In that picture, we can see good friends. But how can we be a good friend? What do we need to do in order to be good friends? Well, we need to call a friend and ask them, How are you? We need to show interest to our friends. And how do we do that? We can call them and ask them, How are you? How are you feeling today? You good? You're great? You're fantastic? Or you're not so good? So remember to call your friends and ask them how they are. What am I good at? I'm good at many things. But let's play a game and see if you can find what am I good at. I'm good at something that needs colour, brush and paper. What am I good at? Can't that be a sport? Hmm, I don't think so. Remember, I need colour, brush and paper. Exactly. I'm good at painting. Because at painting we use colours, brush and paper. Very well done. Now, I'm also good at English, German and French. What are these? Are these musical instruments? No, they're not. Remember, English, French and German. What am I good at? I'm good at languages. Are you good at languages? Well, if you're watching that video, I think you're very good at languages. Now, what can we see in the yellow box? We see some numbers. One, two, three. Two plus seven minus one equals eight. Three times three equals nine. What are these? What am I good at? Very good. I'm good at maths. Are you good at maths? I'm sure you are, because they're very, very important. I'm also good at football, judo and tennis. What are these? Do you remember, some of my students were good at football and judo. What are these? Very well done. These are sports. I'm good at sports. What are you good at? I'm sure you're good at many things. I think you are very good at languages. I think you're very good at maths. I think you're very good at sports. And I think you're a very good friend and a very good student. And a very good grandchild. So, what have we learned today? What can you do after that lesson? You can do many things. You can talk about what you like. For example, do you like cooking? Do you like music? Or do you like sports? You can say what you can do. Do you remember my students? Exactly. And you can do many things. Some of you can cook. And some of you can paint. And I'm sure some of you can play football and basketball really well. And you can also say what you are good at. Some of you are good at languages. I have a student that speaks four languages. He's very good at languages. Are you good at languages? And some of you are very good children and friends. Remember what I told you before. We're all champions. And we're champions outside. We're champions at school. And we're champions at home. Thank you very much. Bye, everyone!